(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
In the current administration, the Presidency of this Court has made efforts to support a major project to adapt the "Journal of the Federal Regional Court of the 3rd Region" by implementing the Open Journal Systems (OJS) platform, internationally used, open-source software, recommended for the management and electronic publication of journals, with the aim of covering all the essential actions for the automation of publishing activities. To crown this initiative, we took advantage of the launch of this first issue in the new digital format to publish a special edition to commemorate the 35th anniversary of the 1988 Federal Constitution. Thus, all the articles and judgments selected address relevant constitutional issues, discussing invaluable achievements and remaining challenges. For all these reasons, this issue represents a milestone in the history of the Journal, which was launched in 1990 as the official repository of case law of this Court. Over the course of more than 30 years of publication, it has undergone several transformations in order to satisfactorily fulfill its institutional mission, always in an attempt to keep up with technological developments and the Judiciary in order to better meet the needs and interests not only of the members of the institution, but of society as a whole.